The Evolution of Tragedy: From Aristotle to Shakespeare and Beyond (Eurasian Journal of Learning and Academic Teaching, 2024)
This article traces the evolution of tragedy from its classical origins in ancient Greece to its contemporary manifestations. Beginning with Aristotle's foundational definition and analysis in "Poetics," the discussion moves through the Roman contributions of Seneca, which influenced Renaissance drama. It examines the profound impact of William Shakespeare's tragedies, highlighting his innovations in character complexity and psychological depth. The article then explores the shifts in tragic narrative during the modern era, with existentialism, absurdism, and realism introducing new dimensions to the genre. The works of Henrik Ibsen, Anton Chekhov, Samuel Beckett, and contemporary playwrights such as Arthur Miller are analyzed for their contributions to the evolving tragic form. The enduring power of tragedy to reflect and interrogate the human condition is emphasized, underscoring its continual adaptation to cultural and artistic changes. This exploration reveals the timeless quest of tragedy to evoke empathy, contemplation, and catharsis, maintaining its relevance across centuries. Tragedy, as a literary form, has captivated audiences for centuries with its profound exploration of human suffering and the inexorable nature of fate. From its classical origins in ancient Greece to the masterpieces of William Shakespeare and beyond, the evolution of tragedy reflects the shifting paradigms of cultural, philosophical, and artistic values.